2019
DOI: 10.2196/13734
|View full text |Cite
|
Sign up to set email alerts
|

Home Virtual Visits for Outpatient Follow-Up Stroke Care: Cross-Sectional Study

Abstract: BackgroundTimely, in-person access to health care is a challenge for people living with conditions such as stroke that result in frailty, loss of independence, restrictions in driving and mobility, and physical and cognitive decline. In Southeastern Ontario, access is further complicated by rurality and the long travel distances to visit physician clinics. There is a need to make health care more accessible and convenient. Home virtual visits (electronic visits, eVisits) can conveniently connect physicians to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
96
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(108 citation statements)
references
References 22 publications
10
96
1
1
Order By: Relevance
“…In fact, it was robustly reported that video visits were way better than a phone call. This aligns with other studies that have noted the value of assessing patients in their own homes 6,23,24 by, for example, helping identify safety issues, verifying patients' medications, 25 and involving family members on the call. 26 Providers also expressed that there is huge potential for video visits, given the increased ability to monitor health data remotely, such as gait sensors and applications for commercially available smart devices to track movement.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In fact, it was robustly reported that video visits were way better than a phone call. This aligns with other studies that have noted the value of assessing patients in their own homes 6,23,24 by, for example, helping identify safety issues, verifying patients' medications, 25 and involving family members on the call. 26 Providers also expressed that there is huge potential for video visits, given the increased ability to monitor health data remotely, such as gait sensors and applications for commercially available smart devices to track movement.…”
Section: Discussionsupporting
confidence: 86%
“…This could result in further barriers to appropriate and timely care. 1,25 Video visits, however, have the potential for saving patients and/or their caregivers travel time and associated outof-pocket and health care costs. 1,5,8,23,25 Providers also reported innovating on physical examination techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our pilot study demonstrated a very high degree of patient satisfaction, reduction in per capita health care costs, out of pocket expenses [mean(SD): $74.92(57.99) CND; median(IQR): $52.83(31.26-94.53) CND], health system costs (range between $23,832 to $28,584 dollars, just from the pilot), and statistically significant reduction in wait times for an eVisit follow-up compared to in-person follow-up. 11 Physicians were able to assess patients more quickly via eVisit than via an in-person encounter, thus increasing the timely availability of health care. 12 Adopting virtual care solutions can also result in a significant reduction in costs.…”
Section: Our Experience With Virtual Care In Neurologymentioning
confidence: 99%
“…To meet our ethical responsibilities to provide equitable care for all people, innovations have occurred. While we continue to see patients requiring nondeferrable care in person in our clinics, we have expanded our use of video visits 14 and other e-health tools. However, most procedures and many critical patient-doctor interactions must occur in person, and these have been delayed.…”
Section: Introductionmentioning
confidence: 99%